An Investigation of Higher Vocational Education EFL Teachers: Experiences and Challenges in Using AI for English Grammar Teaching and Learning - Zhang , Ling; Mohammed, Lubna Ali; Qasim, Awais (Journal of Ecohumanism, 2024)
The emergence of large language models like Ernie Bot presents a promising opportunity to revolutionize the teaching and learning of English as a Foreign Language (EFL), particularly in the area of grammar. This study explores the perspectives of EFL instructors on integrating Ernie Bot into English grammar instruction. The research focused on experienced EFL teachers at Zhengzhou Institute of Technology, Henan, China, who have incorporated Ernie Bot into their writing courses. To gain a comprehensive understanding of their experiences, the study employed a mixed-methods approach. Online surveys provided quantitative data on teachers’ overall impressions of Ernie Bot’s usefulness, while structured interviews offered qualitative insights into their thoughts on integrating the tool into their writing lessons. The findings reveal a strong enthusiasm among EFL instructors at Zhengzhou Institute of Technology regarding the potential of Ernie Bot to enhance grammar instruction. However, the research also highlights the critical need for professional development programs to equip educators with the necessary knowledge and skills. By providing teachers with a thorough understanding of Ernie Bot’s capabilities, limitations, and potential pitfalls, we can ensure its successful implementation and maximize its impact on student learning outcomes.